DIGITAL SCHOOL AS NEW ORGANIZATION BASED ON TECHNOLOGIES OF INFORMATION AND COMMUNICATION - Mamani, Loreta; Cipi, Eva (European Scientific Journal, ESJ, 2014)
As an organization the schools need to change focus and develop into a skills- and competence-based environment. At the same time both teachers and the school as such are met with demands of increased professionalism, internationalization, etc. The task of the school is to provide students with an opportunity to develop the skills necessary to become independent and active citizens in the network society. This requires rethinking the structure of the school, rethinking the organization of learning and the content of the learning process as well as the roles of teachers and students. The content and concepts of the school subjects are developed in the light of information technology and globalization. This work propose some visions for your school regarding the initiatives that are needed to disseminate the evaluation culture both with regard to tools and improvement of the colleagues’ qualifications.